Dampak Konten Mikrofeminisme terhadap Kesadaran Gender Generasi Z: Peran Mediasi Keterlibatan Sosial dan Norma Sosial - Rahmadani, Pinastika; Pamungkas, Yoma Bagus; Julianto, Edi Nurwahyu (LPPM Universitas 17 Agustus 1945 Semarang, 2025)
Gender inequality remains a pressing global issue. Amid the rise of social media, microfeminism emerges as a form of digital activism rooted in personal narratives and everyday resistance. This study aims to examine the impact of microfeminist content on gender awareness among Generation Z in Indonesia, with online social engagement and digital social norms as mediation variables. A quantitative explanatory approach was used, involving 384 respondents recruited through purposive sampling. Data were collected via online questionnaires and analyzed using Generalized Structured Component Analysis (GSCA). The findings indicate that microfeminist content influences gender awareness both directly and indirectly. Online social engagement proved to have the strongest mediating effect, while digital social norms also contributed significantly. These results underscore the importance of participatory interaction and collective norms in shaping gender equality values in digital spaces.